PTU-002 Does open access influence the citation metrics in gastroenterology journals?. (17th June 2017) - Sanders, DS; Menic, N; Nyamali, I; Punnamkuzhy, JM; Whelpdale, P; Kurien, M
Abstract : Introduction: Improving the dissemination and impact of medical research is important, if maximal benefits are to be achieved for patients. To help achieve this goal, researchers are increasingly being asked to make their work open access, or publish in one of the increasing number of open-access journals. The costs associated with open access can be significant, with this financial burden deferred to the submitting research teams. Currently, uncertainty exists as to whether the practice of open access actually adds value to the overall citation metrics. This study addresses this knowledge gap by evaluating outcomes of open access publications in leading gastroenterology journals. Method: Original research articles published in Gastroenterology, GUT and the American Journal of Gastroenterology (AJG) (2009–2013) were reviewed in October 2016. Publications were examined to determine their status as being open access and to assess their study type (clinical research vs basic science). Publications were then cross referenced with the Web of Science TM database to determine overall citation rates. Statistical analyses were performed using contingency tables, using SPSS version 20.0. Chi- sqaured testing was used to assess categorical variables, with a Mann-Whitney U Test (non-parametric testing) used to compare citation rates between open and non-open access publications. p<0.05 was considered significant. Results: 3057 original research articles were published between Jan 2009-Dec 2013 (Gastroenterology (n=1431), GUT (n=732), AJG (n=894). Of these, 154 (5.0%) were open access publications (Gastroenterology (n=13), GUT (n=70), AJG (n=71). The year of publication did influence the frequency of open access publications x 2 (4)=28.7, p<0.0001, with 64.9% (n=100) of open access publications being clinical research studies. Overall, open access publications in the three journals had significantly higher citation rates than non-open access publications (median citation rate: 38.5 vs 33, p=0.044). Conclusion: This is the first study to evaluate the citation metrics for open access publications in leading gastroenterology journals. Based on our findings, authors should be encouraged to make their work open access. Given the merits of open access publications both to patients and researchers, questions should be asked as to whether the high costs of making publications open access is really justifiable. Disclosure of Interest: None Declared